Preparation and photoluminescent analysis of Sm3+ complexes based on unsymmetrical conjugated chromophoric ligand - Hooda, Anjli; Nehra, Kapeesha; Dalal, Anuj; Singh, Sitender; Bhagwan, Shri; Jakhar, Komal; Singh, Devender (Journal of materials science. Materials in electronics, 2022)
The octa-coordinated complexes of Sm(III) with β -diketone and nitrogen-heterocyclic bidentate auxiliary moiety were prepared and characterized spectroscopically. Spectral outcomes of complexes have suggested the isostructural behavior of ternary complexes. Optical bandgap ( E g ) values of complexes were evaluated from Tauc’s plot. The photoluminescence emission spectra of ternary complexes show Sm 3+ -based peaks at 566, 601, 648, and 707 nm attributed to 4 G 5/2 → 6 H J ( J = 5/2–11/2) transitions. Most intense peak at 648 nm is responsible for orange-red emanation of samarium complexes. Colorimetric analysis of complexes supports the results of emission spectra. The fascinating optical properties of ternary metal complexes in the orange-red visible spectral region might be valuable in designing optoelectronic devices and displays.